KEAJAIBAN BULAN DALAM PANDANGAN AL-QUR’AN DAN ASTRONOMI MODERN - Falka Mirza Maulana ARIS BUDIANTO; Faisal Abdullah (BAMALA Institute, 2025)
The Moon is the closest celestial body to Earth and plays a significant role in both cosmic systems and human life. In the Qur’an, the Moon is described as one of God’s signs that reflects the order and precision of the universe. This study aims to examine the Qur’anic depiction of the Moon and analyze its relevance to modern astronomical findings. The research employs a qualitative method using a library research approach by analyzing Qur’anic verses related to the Moon, classical and contemporary Qur’anic commentaries, and modern astronomical literature. The findings indicate that the Qur’an’s description of the Moon’s reflected light, phases (manāzil al-qamar), orbital motion, and function as a timekeeper aligns with modern scientific explanations. Furthermore, modern astronomy reveals the Moon’s crucial role in maintaining Earth’s rotational stability, axial tilt, and tidal phenomena. This study concludes that although the Qur’an is not an astronomy textbook, it presents a coherent cosmic framework that corresponds with scientific realities and supports constructive dialogue between revelation and science.